(untitled) (Italian Journal of Public Health, 2010)
In this special issue the four articles focus on population health in terms of primary care and preventive medicine. This critical area of health often receives less attention than health care issues (more so in the popular press but also in academic analyses).Upon reviewing these very interesting and illuminating articles it was striking that despite significant cultural, economic, geographic and historical differences there are many commonalities which exist throughout the Americas.